TINJAUAN YURIDIS UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA TERKAIT KEGIATAN POLITIK PRAKTIS DI INDONESIA - Putu Ocha Dana Parwata; Adnyani, Ni Ketut Sari; landrawan, I Wayan; Kusuma, Putu Riski Ananda (Jurnal Ilmu Hukum Sui Generis, 2024)
This research aims (1) to find out and analyze the basic considerations for Law Number 5 of 2014 which does not allow ASN to take part in political activities. (2) to find out and analyze the legal consequences of ASN involved in practical political activities. The type of research used by researchers is normative legal research, namely through a statutory regulation approach and a comparative approach. The sources of legal material used are the 1945 Constitution, Law Number 5 of 2014, Law Number 7 of 2017, Law Number 2 of 2011. The results of the research show that (1) Legally normative, Corps Spirit Development and the Civil Servant Code of Ethics which explicitly states that ASN/PNS are obliged to avoid conflicts of personal, group or class interests. Therefore, ASN is prohibited from carrying out actions that lead to partiality with one of the candidates or actions that indicate being involved in practical politics/affiliating with a political party. And explicitly states that ASN must be neutral. (2) In connection with sanctions for State Civil Apparatus who are not neutral, the Minister for Administrative Reform issued a Circular Letter from the Minister for Administrative Reform Number: SE/18.1/M.PAN/5/2004. This circular regulates the criteria for imposing sanctions on state civil servants who are not neutral. The criteria for these sanctions are severe disciplinary punishment, demotion to one level of rank, severe disciplinary punishment in the form of dismissal, severe disciplinary punishment in the form of dishonorable dismissal as a Civil Servant.